PENERAPAN PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATAN AKTIVITAS BELAJAR DAN HASIL BELAJAR ILMU KIMIA SISWA SMAN 1 NATAR LAMPUNG SELATAN - Dwi Yulianti (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2010)
Abstrak: Tujuan penelitian ini adalah untuk membelajarkan siswa dengan pembelajaran kooperatif tipe STAD guna meningkatkan aktivitas belajar siswa, hasil belajar kognitif siswa, dan persentase jumlah siswa yang mendapat skor hasil belajar di atas 64 siswa kelas X.2 dan X.3 di SMAN 1 Natar Lampung Selatan.ÃÂ Untuk mencapai tujuan penelitian dilakukan penelitian tindakan kelas pada kelas X.2 dan X.3 di SMAN 1 Natar Lampung Selatan. Penelitian dilakukan sebanyak tiga siklus pada tahun pembelajaran 2005/2006. Tahap-tahap tindakan yang dilakukan pada setiap siklus dimulai dari: 1) tahap perencanaan tindakan, 2) tahap pelaksanaan tindakan dan observasi, 3) evaluasi, dan 4) refleksi. Indikator keberhasilan tindakan adalah: 1) ada peningkatan aktivitas belajar sebesar 5 persen, 2) ada peningkatan rerata hasil belajar kognitif sebesar 5 angka (skor) dibandingkan dengan hasil belajar kognitif pada siklus sebelumnya, dan 3) ada peningkatan persentase jumlah siswa yang memperoleh skor di atas 64, sebesar minimal 5 persen dari siklus ke siklus. Berdasarkan hasil analisis data diketahui bahwa: 1) peningkatan aktivitas belajar dari siklus satu ke siklus dua berada antara 2,76% sampai 10,71%, dan peningkatan aktivitas belajar dari siklus dua ke siklus tiga berada antara 0,21% sampai 4,48%, 2) peningkatan rerata skor hasil belajar dari siklus 1 ke siklus 2 sebesar 6,39 angka, dan peningkatan rerata skor hasil belajar dari siklus 2 ke siklus 3 sebesar 6,29, dan 3) peningkatan persentase siswa yang memperoleh skor >64 dari siklus satu ke siklus dua sebesar 6,06%, dan peningkatan persentase siswa yang memperoleh skorÃÂ >64 dari siklus dua ke siklus tiga sebesar 8,85%. Kesimpulan penelitian ini adalah bahwa pembelajaran kooperatif tipe STAD dapat meningkatkan aktivitas belajar siswa, meningkatkan hasil belajar kognitif siswa, dan sekaligus meningkatkan persentase jumlah siswa yang mendapat skor hasil belajar di atas 64 siswa kelas X.2 dan X.3ÃÂ di SMAN 1 Natar Lampung Selatan.Kata kunci : strategi mengajar, pembelajaran kooperatif, penelitian tindakan kelas, hasil belajarÃÂ Abstract: The purpose of this study is to facilitate students to learn with the STAD type of cooperative learning in order to improve students' learning activities, enhance studentsÃ¢â¬â¢ cognitive achievements, and increase the percentage of students who obtained a score above 64 of students classroom X.2 and X.3 at SMAN 1 Natar South LampungÃÂ .ÃÂ To achieve the goals of the research conducted classroom action research on classroom X.2 and X.3 at SMAN 1 Natar South Lampung.ÃÂ Research was conducted for three cycles of the academic year 2005/2006.ÃÂ Stages of the action taken on each cycle starts from: 1) the action planning phase, 2) phase of the implementation of actions and observations, 3) evaluation, and 4) reflection.ÃÂ Indicators were measures of success: 1) an increase of five per cent of learning activities, 2) an increasing cognitive achievements mean of five digits (score) compared with the cognitive achievements in the previous cycle, and 3) an increasing percentage of the number of students who obtained a score above 64, for a minimum of 5 percent from cycle to cycle.ÃÂ Based on the results of data analysis found that: 1) there was an increased in activity of learning from first cycle to second cycle were between 2.76% to 10.71%, and an increased in activity cycle of learning from second to third cycles were between 0.21% to 4.48ÃÂ %, 2) there was an increased in mean score of learning outcome from first cycle to second cycle of 6.39 points, and an improved in mean score of achievements from second cycle to third cycle for 6.29, and 3) there was an increased the percentage of students who obtained a score above 64 fromÃÂ first cycle to second cycles of 6.06%, and an increased the percentage of students obtained a score above 64 from second cycle to third cycles of 8.85%.ÃÂ The conclusion of this study is that type STAD cooperative learning can improved studentsÃ¢â¬â¢ learning activities, enhanced students' cognitive achievements, and increased the percentage of students who obtained score above 64 of students achievements at classroom X.2 and X.3 SMAN 1 Natar South Lampung.ÃÂ ÃÂ ÃÂ Keywords:ÃÂ ÃÂ teaching strategy, cooperative learning, classroom action research, cognitive achievement.